Effect of readmissions on increasing hospital admissions for asthma in children. Issue 9 (September 1995) - Senthilselvan, A
Abstract : BACKGROUND–Previous studies have reported increases in the number of hospital admissions for asthma in children. The aim of the present study was to examine the effect of readmissions on these increased hospital admissions and to investigate gender differences in asthma readmissions. METHODS–The Provincial Government of Saskatchewan provides universal health care to its residents. Hospital admissions data for asthma were obtained from the Saskatchewan Health Department for all 134 hospitals in the province between 1980 and 1989. Age-specific and sex-specific hospital admission rates for asthma were calculated for each calendar year using first admissions and all admissions. The ratio between the number of readmissions and all admissions in a year was defined as the readmission rate for that year. RESULTS–Although rates based on all admissions for asthma were greater than rates based on first admissions, trends and sex differences were similar for the two rates. Despite the higher hospital admission rates for boys aged 10-14 years, girls in this age group had higher readmission rates for asthma from 1981 to 1989 (odds ratio (OR) 1.6 for girls; 95% confidence intervals (CI) 1.3 to 1.9). Similar increases were observed in readmission rates for asthma among children aged 5-9 years from 1985 to 1989 (OR 1.3 for girls; 95% CI 1.1 to 1.5). CONCLUSIONS–Readmissions for asthma do not seem to explain the increasing trend in hospital admissions for asthma in children. In children aged 10-14 years girls had higher hospital readmission rates for asthma than boys, and further studies are required to find factors related to the increased readmissions among girls in this age group.